Toll-like receptor 9 expression and activation in acute coronary syndrome patients on dual anti-platelet therapy. Issue 148 (December 2016) - Hally, Kathryn E; La Flamme, Anne C; Larsen, Peter D; Harding, Scott A
Abstract: Introduction: The Toll-like receptor 9 (TLR9) pathway can activate platelets but its role in acute coronary syndromes (ACS) is unknown. This study examined TLR9 expression and platelet activation in response to ODN2006, a TLR9 agonist, in healthy subjects and in ACS subjects treated with dual anti-platelet therapy (DAPT). Materials and methods: TLR9 expression was examined in both resting and thrombin receptor activator peptide (TRAP)-activated platelets (1 and 10 μM) from healthy and ACS subjects by flow cytometry. In both cohorts, ODN2006-mediated platelet activation (5 μM) was examined in whole blood (WB) and platelet-rich plasma (PRP) using cell-surface CD62p and CD63 expression by flow cytometry. Results: Baseline TLR9 expression was significantly greater in ACS subjects compared to healthy subjects (p < 0.01). Following TRAP activation, TLR9 expression increased dose-dependently in healthy subjects. However, no difference in TLR9 expression was seen in ACS platelets following TRAP activation. ODN2006 treatment resulted in significant increases in cell-surface expression of CD62p and CD63 in both WB (all p < 0.001) and PRP (all p < 0.001) in comparison to unstimulated platelets in healthy subjects. Despite DAPT, ODN2006 treatment produced significant increases in both activation markers in the ACS cohort across WB and PRP (all p < 0.0001). Elevated baseline expression of TLR9 in ACS platelets may indicate increased sensitivity to TLR9 agonists and contribute to increased platelet activation in these patients. Furthermore, ODN2006 stimulation can activate platelets in ACS subjects despite treatment with DAPT. Conclusion: This study demonstrates TLR9 expression and activation to be of potential therapeutic importance in ASC patients. Highlights: Platelet activation is central to forming thrombi in acute coronary syndromes (ACS). Platelet-TLR9 expression is elevated in ACS and following platelet activation. ACS platelets become activated in response to ODN2006, a TLR9 agonist. This activation occurred despite optimal treatment with dual antiplatelet therapy. TLR9 expression and activation is of potential therapeutic importance in ACS.